2016
DOI: 10.4269/ajtmh.15-0837
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Profile of Persons Living with Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome and Histoplasmosis from a Colombian Hospital

Abstract: Abstract. Histoplasmosis is common among persons living with human immunodeficiency virus/acquired immune deficiency syndrome (PLWHA) in Latin America, but its diagnosis is difficult and often nonspecific. We conducted prospective screening for histoplasmosis among PLWHA with signs or symptoms suggesting progressive disseminated histoplasmosis (PDH) and hospitalized in Hospital La María in Medellín, Colombia. The study's aim was to obtain a clinical and laboratory profile of PLWHA with PDH. During 3 years (May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 33 publications
2
28
0
7
Order By: Relevance
“…Histoplasma capsulatum, the etiologic agent of histoplasmosis, is a dimorphic fungus endemic in the Mississippi and Ohio River Valleys of the United States, [432][433][434] in many areas of Latin America, [435][436][437] Africa, 438 and more recently in China 439 and Southeast Asia. 432,440 Histoplasmosis is rare in Europe, 441 except when acquired in other endemic areas.…”
Section: Histoplasmosismentioning
confidence: 99%
“…Histoplasma capsulatum, the etiologic agent of histoplasmosis, is a dimorphic fungus endemic in the Mississippi and Ohio River Valleys of the United States, [432][433][434] in many areas of Latin America, [435][436][437] Africa, 438 and more recently in China 439 and Southeast Asia. 432,440 Histoplasmosis is rare in Europe, 441 except when acquired in other endemic areas.…”
Section: Histoplasmosismentioning
confidence: 99%
“…[ 5 ] In French Guiana, among consecutive HIV patients hospitalized for infectious symptoms (fever, isolated or with other symptoms), 42% of those with CD4<200 had culture-confirmed histoplasmosis, and 85% of those with CD4<50 had histoplasmosis[ 6 ]; In Fortaleza, of 378 consecutively admitted HIV patients, 164 (43%) had microscopically confirmed histoplasmosis[ 7 ]; In Panama, 7.65% of patients with an HIV infection had culture-positive H . capsulatum [ 8 ], in Guatemala, and in Colombia histoplamosis and TB are the main opportunistic infections;[ 9 , 10 ] In Venezuela, in patients with AIDS, histoplasmosis was documented in 29 of 66 (44%) autopsies performed[ 11 , 12 ]. Most histoplasmin prevalence studies took place before the AIDS epidemic was identified, because histoplasmin testing is no longer performed.…”
Section: Introductionmentioning
confidence: 99%
“…In persons living with HIV/AIDS (PLWHA), the mycosis often produces a severe clinical form of disease called progressive disseminated histoplasmosis (PDH), which has a high mortality if treatment is not initiated promptly [4] , [5] . As has been previously reported, PDH symptoms are nonspecific, and among PLWHA, symptoms may be similar to those observed in other infectious diseases, thus complicating diagnosis and treatment [4] , [6] , [7] , [8] . In Colombia and other endemic countries in the Americas, where access to antiretroviral therapy (ART) can be limited, histoplasmosis is a cause of high morbidity and mortality (up to 30%) in PLWHA [9].…”
Section: Introductionmentioning
confidence: 99%